Centromere regulation: new players, new rules, new questions - Pauleau, Anne-Laure; Erhardt, Sylvia (European journal of cell biology, 2011)
Centromeres support the assembly of the kinetochore on every chromosome and are therefore essential for the proper segregation of sister chromatids during cell division. Centromere identity is regulated epigenetically through the presence of the histone H3 variant CENP-A. CENP-A regulation and incorporation specifically into centromeric nucleosomes are the matter of intensive studies in many different model organisms. Here we briefly review the current knowledge in centromere biology with a focus on Drosophila melanogaster and how these insights lead to new rules and challenges.
Gesehen am 28.09.2022